Isolasi dan Identifikasi Senyawa Metabolit Sekunder dari Rimpang Temu Hitam (Curcuma aeruginosa Roxb) - Yuwinda Cindy Elisabet Panggabean; Eva Marliana; Rita Hairani; Swandari Paramita; Sjarif Ismail (JURNAL KIMIA MULAWARMAN, 2020)
Isolation and identification of secondary metabolites from ethyl acetate fraction of rhizomes of Temu Hitam (Curcuma aeruginosa Roxb.) have been done. The separation of ethyl acetate fraction and further seperation were performed using gravity column chromatography with n-hexane and ethyl acetate (9.5:0.5-3:7) as solvent systems to obtain the isolate (oil;0.0216 g). Based on UV analysis of isolate, the result showed 1 peak at ? 206.14 nm. In addition, the FT-IR spectra indicated the presence of functional groups of OH, aliphatic C-H, C=O and C-O. According to the result of the UV and FT-IR spectra, the isolate can be identified as terpenoid.